Rentabilidad de las operaciones de microcrédito de las Cooperativas de Ahorro y Crédito y su impacto socio-económico en el cantón La Maná periodo 2017-2018. - Reina Rivera, Milena Guadalupe (2019)
The present research entitled, "Profitability of the microcredit operations of the Savings and Credit Cooperatives and their socio-economic impact in La Maná Period 2017 - 2018" evaluates the socio-economic impact of the microcredits granted by the cooperatives of savings credit in La Maná. Savings and Credit Cooperatives are companies that are part of the Ecuadorian Financial System and whose corporate purpose is to serve the financial needs of its members and third parties through the exercise of the activities of credit institutions. The need arises to propose a Profitability manual based on credit and collections policies to improve the profitability of the microcredit portfolio of savings and credit cooperatives aimed at satisfying the needs of the population, which is where the problem arises: How does the profitability of the microcredit operations of the Savings and Credit Cooperatives in the socio-economic development of La Maná affect? The objective is stated, which is to determine the impact of profitability in the microcredit operations of the Savings and Credit Cooperatives, for the elaboration of a proposal aimed at strengthening its socio-economic impact in La Maná Period 2017 - 2018. Based on the research, the proposal called A MODEL OF MANAGEMENT TO IMPROVE THE PROFITABILITY OF THE PORTFOLIO OF THE MICROCREDITS OF THE SAVINGS AND CREDIT COOPERATIVES is made, based on the operational principles that govern cooperativism, the proposal that is structured responds to a purpose of the Profitability manual based on credit and collections policies. The topics that are included are of great importance for managers, assemblies, management personnel, even for partners interested in better understanding the management of credit. The methods and techniques used in the present investigation were applied based on the need for information to be obtained, as well as the formal interview, questionnaires prepared for the survey and field observation. We used the inductive method that allowed us to start from the analysis of a particular case and observe the existing reality, the hypothetical-deductive method to pose a problem through an induction process, the qualitative method to qualify and describe the social phenomenon based on determining features, the analytical method to explain the causes of the events or phenomena that constitute the whole. The direct beneficiaries in this project constitute the 14 Savings and Credit Cooperatives of La Maná Canton and each one of the people that make it up, the society that with the presence and development of the savings and credit cooperatives constitute generating entities of economic development (42,216 inhabitants according to the 2010 INEC census), 1200 students and 60 research teachers, and the Technical University of Cotopaxi with the generation of knowledge.